EVALUASI KUALITAS DAN KETERSEDIAAN AIR PULAU KARIMUNJAWA-KEMUJAN KEPULAUAN KARIMUNJAWA, KABUPATEN JEPARA - Hartanto, Priyo; S, I. Hadi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
Karimunjawa islands became an important area since it decided as a part of Karimunjawa National Park area so that become an area of tourism on the base sea resources. From morphogenetic point of view, Karimunjawa-Kemujan Islands is an petabah type islands, which is characterized by the wide about 20,8 km2 and 11,4 km2, and it can be classified as a small islands. Lithologically, these islands consists of sandstone, sandstone interbaded, clay, metamorphic and granitic rocks. The avarage of annual rain up to 3120 mm with total of rain days for a year is 114 days, so that water resources Island in Karimunjawa-Kemujan are very limited. Shallow groundwater zone with limited potensial and locally distributed in plain morphology can be get at less then 10 meters in depth. In general, the water quality in Karimunjawa-Kemujan islands still good as the standard of drinking water. From this research, the groundwater in Karimunjawa island can be grouped to 3 zones which it based on Electrical Conductivity values that are: (a) zone of 1054-2250 mS/cm, (b) zone of 100-1000mS/cm and zone of 57-59,6 mS/cm. In the other, EC value of water in Kamujan island generally is less than 100 mS/cm.